An Evaluation of the Definition of Agreement in the Indonesian Civil Code and Implications for Legal Certainty in Economic Interactions of Indonesia - Syafiuddin, Afif; Alladuniah, Muhammad Ali (Faculty of Law, Universitas Pattimura, 2025)
Introduction: Article 1313 of the Indonesian Civil Code defines an agreement as an act by which one or more persons bind themselves to one or more other persons. This definition is often considered overly general and inadequate to reflect the complexities of modern society and economic dynamics.Purposes of the Research: This research evaluates the legal understanding of agreements in Article 1313 of the Civil Code and analyzes its implications for legal certainty in economic interactions of Indonesia.Methods of the Research: A normative juridical research method was employed, involving an analysis of legal literature, expert doctrines, and legal practices in Indonesia.Results Main Findings of the Research: Findings indicate that the definition of an agreement in Article 1313 of the Civil Code is no longer relevant and leads to legal uncertainty in economic transactions, which hinders business and investment certainty. A more concrete and adaptive reformulation of the agreement's definition is necessary to address this gap, with the hope of increasing legal certainty in economic interactions, as well as supporting economic stability and growth in Indonesia.